PENYUSUNAN INDEKS KEPUASAN MASYARAKAT PADA KOMISI PENYIARAN INDONESIA DAERAH (KPID) PROVINSI JAMBI - Ade Octavia (DIGEST MARKETING, 2017)
The aim of this research is measure and analyzes the citizen satisfaction index in Province Jambi. Survey was implemented as research methode where sample consist of 150 sampling unit, that cinsist of publicbroadcasters of Television and Radio and other govermental relatied instituttion. Instrument use to measure is the ministerial decree: Kep/25/M.PAN/2/2004. The result shows that there are eighteen satisfied indicators, they are: servicing procedures ease, common terms, clarity and certainty of employees, discipline, responsbility, fairness, courtesy and friendliness, location and physical building, personnel readiness, environmental comfort, security environment, cooperation, control broadcast content, interaction, dissemination of information, follow up complaints and ease of getting information. Otherwise, there are two elements those unsatisfied, they are public speed of service and assurance service schedules. Hence, it is recommended that KPID continously to improve service performance. . Keywords: Performance, Public Service, good governance